A Hybrid Silicon Single‐Mode Laser with A Racetrack Ring and Periodic Slots. Issue 9 (27th June 2013) - Zhang, Yejin; Wang, Hailing; Qu, Hongwei; Zhang, Siriguleng; Zheng, Wanhua
ABSTRACT In this letter, a novel III‐V/silicon hybrid single‐mode ring cavity laser is presented. The on‐chip racetrack ring electrically pumped laser does not rely on facet polishing and dicing to define the laser cavity. The mode selected mechanism is based on a racetrack resonator with periodic slots. The fabrication of the laser only needs standard photolithography in the whole technological process. The side mode suppression ratio of larger than 20 dB is obtained from experiment. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2141–2143, 2013